Protective effect of trimetazidine on myocardial mitochondrial function in an ex-vivo model of global myocardial ischemia - Monteiro, P (2004)
Trimetazidine is an anti-ischemic drug whose cytoprotective mechanisms are not yet fully understood (but until now mainly related to the trimetazidine-induced "metabolic shift" from lipid beta-oxidation to glucose aerobic oxidation). We studied the effect of trimetazidine on the mitochondrial function of ischemic Wistar rat hearts perfused with glucose, using a model of ex-vivo perfusion (Langendorff system). We measured the electrical potential of the mitochondrial membrane, O2 consumption by the respiratory chain, energy charges generated and the enzyme activities of the respiratory chain complexes. In this model, trimetazidine had a preferential action on the oxidative system (mainly on complex I), increasing its enzyme activity and decreasing O2 consumption after phosphorylation; this could decrease oxygen free radical production and increase mitochondrial integrity, thus allowing the maintenance of the electrical potential. These results allow us to better understand the cytoprotective effects of trimetazidine in coronary artery disease.